2022
DOI: 10.3390/pathogens11070786
|View full text |Cite
|
Sign up to set email alerts
|

Primary Antibiotic Resistance of Helicobacter pylori in Different Regions of China: A Systematic Review and Meta-Analysis

Abstract: Aim: Understanding the prevalence of antibiotic resistance can provide reliable information for selecting treatment options. The goal of this meta-analysis was to observe the primary antibiotic resistance of Helicobacter pylori (H. pylori) in different regions and time periods of China. Method: We searched PubMed, EMBASE, Chinese Biomedical databases and the China National Knowledge Infrastructure from inception to 20 February 2022. Data on the prevalence of H. pylori primary resistance at various time points … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 62 publications
0
37
1
3
Order By: Relevance
“…Primary and secondary resistance to CLA, as well as to MTZ and LEV is higher than 15% in most WHO regions (6, 22). However, in Gipuzkoa, primary resistance to the three most commonly used antimicrobials for H. pylori infection was lower than that reported for other countries (22)(23)(24)(25). This could be, at least in part, due to the performing culture of H. pylori followed by antibiogram in all isolates obtained from biopsies, and accordingly prescribing an antibiogram-guided treatment.…”
Section: Discussioncontrasting
confidence: 55%
“…Primary and secondary resistance to CLA, as well as to MTZ and LEV is higher than 15% in most WHO regions (6, 22). However, in Gipuzkoa, primary resistance to the three most commonly used antimicrobials for H. pylori infection was lower than that reported for other countries (22)(23)(24)(25). This could be, at least in part, due to the performing culture of H. pylori followed by antibiogram in all isolates obtained from biopsies, and accordingly prescribing an antibiogram-guided treatment.…”
Section: Discussioncontrasting
confidence: 55%
“…Although the antibiotic combination partially improves the eradication rate, it is also associated with eradication failure. In China, the drug resistance rates of clarithromycin, metronidazole, and levofloxacin remain high [4] . Specifically, BQT is administered for 10 or 14 days.…”
Section: Introductionmentioning
confidence: 99%
“…The high prevalence of clarithromycin resistance limited the eradication effect [ 13 ]. A systematic review showed that clarithromycin resistance was up to 35% in southwestern China [ 48 ]. In our study, the eradication rate of polaprezinc-containing quadruple therapy was non-inferior to conventional bismuth-containing quadruple therapy (75.0% vs. 87.8%).…”
Section: Discussionmentioning
confidence: 99%